High-Density Genetic Map Construction and Gene Mapping of Basal Branching Habit and Flowers per Leaf Axil in Sesame - Mei, Hongxian; Liu, Yanyang; Du, Zhenwei; Wu, Ke; Cui, Chengqi; Jiang, Xiaolin; Zhang, Haiyang; Zheng, Yongzhan (Frontiers in Plant Science, 2017)
A good genetic map can provide the framework for quantitative trait loci (QTL) analysis, map-based gene cloning, and genome sequence assembling. The main objectives of this study were to develop a high-density genetic linkage map using specific length amplified fragment sequencing (SLAF-seq) in sesame. In the result, a high-resolution genetic map with 9,378 SLAF markers and 13 linkage groups (LGs) was constructed. The map spanned a total genetic distance of 1,974.23 cM, and the mean LG length was 151.86 cM, with an average genetic distance of 0.22 cM between adjacent markers. Based on the newly constructed genetic map, genes for basal branching habit (SiBH) and flowers per leaf axil (SiFA) were mapped to LG5 and LG11, respectively.